AquaNet - Zooplankton from Bolmen AquaNet platform, 2017-06-21–2017-09-19 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2019)
Zooplankton information from grab samples taken from the AquaNet mesocosms. This data contains more specifically the number of individuals per taxonomic unit and biomass calculations.
Bolmen Research Station (2019). AquaNet - Zooplankton from Bolmen AquaNet platform, 2017-06-21–2017-09-19 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/lEOdht0mDvyBTUYEwmkye1VF
Keywords: SITES AquaNet; Ecosystem functions; Food-web dynamics; Zooplankton; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap